Effect of Foliar Application of Zinc and Iron on Seed Yield and Yield Components of Common Bean (Phaseolus vulgaris) - Zahra Yousefi; Peyman Sharifi; Mohammad Rabiee (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2023)
The effects of foliar application of iron and zinc were evaluated on Guilanian landrace of common bean in Rice Research Institute of Iran. A factorial experiment with three replication was conducted based on randomized complete block design. Two doses of Fe as iron chelate (0 and 0.4%) and five doses of Zn as zinc chelate (0, 0.1, 0.2, 0.3 and 0.4%) were sprayed at flowering and pod formation stages. The effects of iron and zinc in foliar form were significant on seed yield, a hundred seed weight and content of zinc and iron in aerial plant parts. The interaction effects of two factors was significant on seed yield, number of pods per plant, plant height, pod length, number of seeds per pod, a hundred seed weight and content of Zn and Fe in aerial parts of plant. In the absent of and 0.4% Fe foliar treatments, the highest value of seed yield were observed when 0.4% and 0.3% zinc were applied, respectively. The content of iron and zinc in aerial parts of plant were increased in line with foliar application of zinc. Spraying 0.4% Fe combined with 0.3% Zn was recommended for the yied improvement on common bean.